Certification exam review for dental assisting : prepare, practice, & pass! - Campbell, Melissa (Boston : Cengage Learning, 2017)
Certification exam review for dental assisting, is designed around the Dental Assisting National Board (DANB) Examination blueprint. Its fresh approach centers on how and what to study to pass a variety of state and regional exams, while eliminating tangential material that can bog down the study process.
Index : page 199-208.
Keywords: Dental Assistants -- education; Certification; Test taking skills